Formalization of Organizations of Recyclers by Trade in Bogota: Reflections from Popular Economy - Luisa Fernanda Tovar (Íconos)
In big global cities, the management of residues is a problem that continues to gain importance. For generations the community of recyclers has taken charge of a labor that, although poorly recognized, generates multiple social, environmental and economic benefits. From a traditional public policy stand point, this activity is considered informal and there is a need to “correct” it through formalization processes that ignores lived realities. This article analyzes integration approaches and the main obstacles of organizations of recyclers in Bogota. It aims to widen analytical perspectives by introducing an interpretation of these processes from the popular economy, which recognize and values not only the activity, but the participation of recyclers as fundamental actors in the co-construction and implementation of public policies that represent an effective improvement of labor conditions and of the livelihoods of this community.